Assessment Of Teachers’ Implementation Of Continuous Assessment In Senior Secondary Schools In Delta Central Senatorial District. - Osadebe, Patrick U.; Oghenekaro Abel., Uvietesivwi (Advances in Social Sciences Research Journal, 2018)
The study investigated the Assessment of Teachers’ Implementation of Continuous Assessment in Senior Secondary School in Delta Central Senatorial District. To guide the study, six research questions were raised and six null hypotheses were formulated. The expost-facto research design was used in the study. The population of the study consisted of 6405 teachers from Public Senior Secondary School in Delta Central Senatorial District. 1024 teachers out of the total population of 6405 were selected through a proportionate stratified sampling technique. A 30-item questionnaire was used to collect data from the selected schools. Mean was used to answer the research questions, while t-test was used to test the hypotheses at 0.05 level of significant. Result of the findings include the following: there was no significant difference between male and female teachers on the implementation of continuous assessment in secondary schools; there was no significant difference between rural and urban teachers’ on the implementation of continuous assessment in secondary schools; there was no significant difference between high and low socio-economic background of teachers on the implementation of continuous assessment in secondary schools; there was no significant difference between single and mixed school teachers’ on the implementation of continuous assessment in secondary schools; there was no significant difference between teachers’ below 30 and 30 years above on the implementation of continuous assessment in secondary schools; there was no significant difference between B.Ed and M.Ed teachers on the implementation of continuous assessment in secondary schools. The study contributed to knowledge because it provides data relating to continuous assessment of teachers for the benefit of educational management; the study has opened a new route about teachers on the implementation of continuous assessment which could be of great help in the management of continuous assessment practices in schools.